2016
DOI: 10.1007/s10195-016-0426-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine consumption may lead to aseptic loosening in proximal mega-prosthetic femoral replacement

Abstract: BackgroundAseptic loosening after total hip arthroplasty is likely related to nicotine ingestion. However, aseptic loosening as a direct consequence of smoking habits has not been described with regard to proximal mega-prosthetic femoral replacement. The aim of the present study was to evaluate the association between nicotine consumption and aseptic loosening rates after proximal mega-prosthetic femoral replacement.Materials and methodsA consecutive series of patients who received mega-prosthetic replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A possible explanation for the decreased probability for aseptic loosening in higher age might be the presumed lower activity in the early postoperative period in this population. Regarding the nicotine consumption, increased risk for aseptic loosening has been shown in proximal mega-prosthetic femoral replacement [ 17 ]. However, nicotine abuse showed no increased probability for aseptic loosening in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for the decreased probability for aseptic loosening in higher age might be the presumed lower activity in the early postoperative period in this population. Regarding the nicotine consumption, increased risk for aseptic loosening has been shown in proximal mega-prosthetic femoral replacement [ 17 ]. However, nicotine abuse showed no increased probability for aseptic loosening in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative offset restoration and early stem subsidence at three months postoperatively were controlled in the AL group. Besides noting the implant details, medical records were screened for postoperative NSAR, age, and nicotine abuse, presenting other assumed risk factors for aseptic loosening [ 15 , 17 19 ]. Furthermore, details were noted for THA indication (primary osteoarthritis or other reason), gender, side, height, weight, and bilateral THA on the same day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While tobacco usage is declining compared to previous years, a recent study reported that approximately 1 in 5 adults in the United States still use tobacco products [ 30 ]. Tobacco usage is a modifiable risk factor in arthroplasty that has been shown to increase risk of aseptic loosening and osteolysis in cemented TKA and increase aseptic loosening in total hip arthroplasty [ 22 , [31] , [32] , [33] ]. Additionally, tobacco usage in patients who undergo total joint arthroplasty results in increased rates of periprosthetic joint infection, readmission, postoperative complications, all-cause revision, and reoperation [ [34] , [35] , [36] ].…”
Section: Introductionmentioning
confidence: 99%